Histopathological and Gastric Histomorphometry Analysis in Mice Colibacillosis Model Induced by Ethanol 96% Oregano Vulgare Extract - Agustin, Yuliana; Amri, Indah Amalia; Dameanti, Fidi Nur Aini Eka Puji; Wisesa, Ida Bagus Gde Rama (Universitas Airlangga, 2022)
Colibacillosis is a disease caused by Escherichia coli which is a normal flora bacterium of the digestive system in humans and animals. Oregano contains carvacrol and thymol which provide an antibacterial. This study was used 20 male Balb/C mice age 2-3 weeks with an average weight of 20-25 grams and were divided into 5 groups with 4 replications: negative control (KN), positive control (KP) given by streptomycin dose of 20 mg/head. E. coli dose of 3 x 109 CFU, (P1) was given by streptomycin dose of 20 mg/head, E. coli dose of 3 x 109 CFU, then given oreganoextract dose of 5 mg/head, (P2) was given by streptomycin dose of 20 mg/head, E. coli dose of 3 x 109 CFU, then given oregano extract dose of 10 mg/head, (P3) was given by streptomycin dose of 20 mg/head, E. coli dose of 3 x 109 CFU, then oregano extract was given dose of 20 mg/head. The data were analyzed by descriptive comparative. The histopathology showed epithelial cell damage or erosion caused by inflammatory cells in KP, P1, P2, and P3. In study group given oregano extract dose of 20 mg/head, P3, inflammatory cells and epithelial erosion were lower. Based on the ANOVA test of day 3 and 6 after necropsy, P1, P2, and P3 show insignificant in villi length and width of the vili (p>0,05) compared to KP. The conclusion the result of the histopathology result is epithelial erosion in group with dose of 20mg/head oregano extract was able to relieve the symptoms of colibacillosis. The conclusion of histomorphometry of the length and width of the villi at P1, P2, P3 (p>0.05) was not significantly different from the positive control.